Introduction of Complete Ration Silage to Substitute the Conventional Ration at Traditional Dairy Farms in Lembang - Hasanah, U.; Permana, I.G.; Despal, (Pakistan Journal of Nutrition, 2017)
Background and Objective: Unsustainable forage supply is one of the limiting factors when providing sufficient nutrients for dairy cattle. Although silage technology has been available for years, their utilization in the traditional dairy farming community of Koperasi Peternak Susu Bandung Utara (KPSBU) Lembang has not been popular. An experiment was conducted to evaluate the impact of collectively made Complete Ration Silage (CRS) to substitute the current ration used by the farmers. Materials and Methods: Three types of rations (R0, R1 and R2) were tested to substitute 0, 20 and 40% of the conventional ration. This experiment used 12 Friesian Holstein cows with initial conditions of 463.28±42.18 kg b.wt., 20±3.27 L daily milk and 1-3 lactation cycle(s) and 3.5±1.6 months in milk. The cows were grouped according to their initial body weight before being assigned to the treatments. The parameters observed in this experiment included the physical and fermentative characteristics of the CRS, nutrient contents, fermentability, digestibility and the intake of the rations. The impact that the rations had on the performances of the cows were observed in terms of manure score, milk production and quality, body weight gain, body condition score and technical and economical feed efficiencies. Results: The results showed that R2 produced significantly higher values (p